2020
DOI: 10.1371/journal.pmed.1003113
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a novel tuberculosis point-of-care urine lipoarabinomannan assay for people living with HIV: A meta-analysis of individual in- and outpatient data

Abstract: Background Tuberculosis (TB) is the most common cause of death in people living with HIV (PLHIV), yet TB often goes undiagnosed since many patients are not able to produce a sputum specimen, and traditional diagnostics are costly or unavailable. A novel, rapid lateral flow assay, Fujifilm SILVAMP TB LAM (SILVAMP-LAM), detects the presence of TB lipoarabinomannan (LAM) in urine, and is substantially more sensitive for diagnosing TB in PLHIV than an earlier LAM assay (Alere Determine TB LAM lateral flow assay [L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 29 publications
8
58
4
1
Order By: Relevance
“…Specificity of FujiLAM in this study with HIV-negative patients was 98.9%, higher than AlereLAM’s specificity at 92.3% ( Figure 2 ). Earlier studies reported a lower specificity for FujiLAM ( 16 , 19 , 26 ) and the result from this study underlines the importance of a very comprehensive reference standard for a proper specificity assessment of urine biomarker tests ( 27 ).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Specificity of FujiLAM in this study with HIV-negative patients was 98.9%, higher than AlereLAM’s specificity at 92.3% ( Figure 2 ). Earlier studies reported a lower specificity for FujiLAM ( 16 , 19 , 26 ) and the result from this study underlines the importance of a very comprehensive reference standard for a proper specificity assessment of urine biomarker tests ( 27 ).…”
Section: Discussionsupporting
confidence: 62%
“…FujiLAM was designed as a rule-in TB diagnostic test to allow rapid treatment initiation and reached a PPV of 95.2%. Together with its high sensitivity for TB diagnosis in people living with HIV ( 19 ) (sensitivity of 70.7% across CD4 strata), the FujiLAM might have considerable impact on the TB epidemic when scaled-up widely for use in near-patient settings. This is supported by a recent impact modeling analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies in HIV-infected outpatients [31] and a recent meta-analysis of 1595 HIV-positive inpatients and outpatients [22] have confirmed FujiLAM's superiority over AlereLAM. The meta-analysis reported 70.7% (95% CI: 59.0-80.8%) sensitivity for FujiLAM, a sensitivity increase of 35.8% compared to AlereLAM [22]. FujiLAM also showed high performance for the detection of EPTB in HIV-infected patients [56].…”
Section: The Need For Next-generation Highly Sensitive and Specificmentioning
confidence: 88%
“…FujiLAM showed approximately 30% improved diagnostic sensitivity in HIV-positive inpatients compared to AlereLAM at 95.7% specificity [27]. Additional studies in HIV-infected outpatients [31] and a recent meta-analysis of 1595 HIV-positive inpatients and outpatients [22] have confirmed FujiLAM's superiority over AlereLAM. The meta-analysis reported 70.7% (95% CI: 59.0-80.8%) sensitivity for FujiLAM, a sensitivity increase of 35.8% compared to AlereLAM [22].…”
Section: The Need For Next-generation Highly Sensitive and Specificmentioning
confidence: 91%